The role of industrial sector in the Brazilian territorial reconfiguration: New expressions for XXI century national dilemmas - Aristides Monteiro Neto; Raphael de Oliveira Silva; Danilo Severian (Institute for Applied Economic Research (ipea), 2022)
In this article, we discuss the current pattern of territorial reconfiguration of the Brazilian industry, its current forms, and motivations in order to problematize some of the most significant challenges of the current regional issue. We have brought new evidence of how it keeps deconcentrating in the context of the persistent decline in the industrial participation in the national economy. We resumed the analysis on the micro-regional scale that showed the following results. 1) Relevant industrial agglomerations (RIAs) continue to flourish in all regions of the country. 2) Their preferred place is no longer the polygonal area of Diniz-Crocco (1996). 3) In terms of industrial job creation, the new RIAs for the period 1995-2015 generated more jobs than those established before 1995.
Keywords: O14; R11; R12; R58; 330; industry and territory; territorial reconfiguration; industrial dynamism; regional development